“Desarrollo de un aplicativo web para el agendamiento de citas médicas dirigido al "Patronato de Amparo Social" del cantón La Maná”. - Loor Cevallos, Angie Nicole (2023)
In the research project, the development of a web application for the scheduling of medical appointments aimed at the "Patronato de Amparo Social" of the La Maná canton was proposed, as it identified a great demand for its medical services, it is required that the information generated by the patients is managed in a technological tool. With the application of research techniques such as: interviews and surveys, the functional and non-functional requirements of the system are established: allowing to know the problems they have in the process of scheduling medical appointments, and the technological tools for their development are defined: Bootstrap as a framework, the programming language PHP, JavaScript, CSS, HTML for the design and development of the application; with its respective MySQL database management system, the same one that was used locally through the XAMPP software and in the cloud through a web server. However, the development of the project was carried out under the agile Scrum methodology through the execution of four Sprints that allowed the development in the management processes of patients, health professionals, statistical assistant and PASGADMLM. Therefore, the web system implemented for appointment scheduling went through black box and white box tests to approve that the functionality is in accordance with the requirements established by the client.